Design and Sustainability - Jagtap, Santosh; Corsini, Lucia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue "Design and Sustainability" aimed to foster discussion on the design and development of products, services and PSS that are socially, economically and environmentally sustainable. It is crucial to consider various facets of design and sustainability in a broad range of sectors and countries, while providing attention to often overlooked 'softer' dimension of social sustainability.